Effect of Combined Mental Task and Metaboreflex Activation on Hemodynamics and Cerebral Oxygenation in Patients With Metabolic Syndrome - Doneddu, Azzurrra; Roberto, Silvana; Pinna, Virginia; Magnani, Sara; Ghiani, Giovanna; Sainas, Gianmarco; Mulliri, Gabriele; Serra, Stefano; Kakhak, Seyed Alireza Hosseini; Milia, Raffaele; Lecis, Romina; Guicciardi, Marco; et al. (Frontiers in Physiology, 2020)
Objective. The hemodynamic response to muscle metaboreflex has been reported to be significantly altered by metabolic syndrome (MS), with exaggerated systemic vascular resistance (SVR) increments and reduced cardiac output (CO) in comparison to healthy controls (CTL). Moreover, patients with MS have proven to have impaired cerebral blood flow in response to exercise. Thus, we wondered whether contemporary mental task (MT) and metaboreflex would result in reduced cerebral oxygenation (COX) in these patients. Methods. In order to find out, 13 MS patients (5 women) and 14 normal age-matched CTL (CTL, 6 women) took part in this study. All the participants underwent 5 different tests, each lasting 12 minutes: post-exercise muscle ischemia (PEMI) to activate the metaboreflex, control exercise recovery (CER), PEMI+MT, CER+MT, and MT alone. During each session, COX was evaluated using near infrared spectroscopy with sensors applied to the forehead. Their hemodynamic parameters were measured using impedance cardiography. Results. The main results show that MS patients had higher SVR and lower CO levels compared to the CTL group during metaboreflex activation. Stroke volume and ventricular filling and emptying rates were also significantly reduced. Moreover, when MT was added to PEMI, COX significantly increased CTL group with respect to the baseline (103.46±3.14%), whereas this capacity seemed to be reduced in MS patients (102.37±2.46%). Conclusions. It was concluded that 1) patients with MS showed hemodynamic dysregulation during the metaboreflex, with exaggerated vasoconstriction, and that 2) MS patients appeared to have reduced capacity to increase COX when a mental task activity superimposed the metaboreflex.